2014
DOI: 10.1089/ten.tea.2013.0703
|View full text |Cite
|
Sign up to set email alerts
|

Can Notochordal Cells Promote Bone Marrow Stromal Cell Potential for Nucleus Pulposus Enrichment? A SimplifiedIn VitroSystem

Abstract: Bone marrow stromal cells (BMSCs) have shown promising potential to stop intervertebral disc degeneration in several animal models. In order to restore a healthy state, though, this potential should be further stimulated. Notochordal cells (NCs), influential in disc development, have been shown to stimulate BMSC differentiation, but it is unclear how this effect will translate in an environment where resident disc cells (nucleus pulposus cells [NPCs]) could also influence BMSCs. The goal of this study was, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…To obtain a better understanding of MSC differentiation into NP-like cells, we investigated the effects of the 50% or 100% NPC conditioned medium on MSCs. Some previous studies showed that the notochordal cells and notochordal cell conditioned medium had positive effects in the treatment of IVD degeneration [ 31 , 32 ]. However, it remains unclear whether these positive effects apply to MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain a better understanding of MSC differentiation into NP-like cells, we investigated the effects of the 50% or 100% NPC conditioned medium on MSCs. Some previous studies showed that the notochordal cells and notochordal cell conditioned medium had positive effects in the treatment of IVD degeneration [ 31 , 32 ]. However, it remains unclear whether these positive effects apply to MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…To date, although a number of studies have shown the activating effects of NCs for the treatment of IDD, the regeneration potential was mild or invalid due to the disruption of the physiological organization of NCs [ 4 , 37 , 38 ]. In this study, cell viability and the expression of NC phenotype-related genes after NC-rich NP explant were tested in rabbit L4/5, L5/6, and L6/7 IVDs; the results demonstrated no significant differences, indicating that the NC-rich NP explant model was comparable among the three segments used in this study and that these could be used randomly.…”
Section: Discussionmentioning
confidence: 99%
“…The co-culture of MSCs with NPCs is often used to differentiate MSCs into NPClike cells. Both direct co-culture [56,57,[177][178][179][180] and trans-well co-culture [72,[181][182][183] successfully induced the chondrogenic differentiation of MSCs. Wharton's jelly is another source of MSCs [184].…”
Section: Conditioned Mediums Exosomes and Co-culturesmentioning
confidence: 99%